Mesin Mini Soaper - Mohammad Noor, Hafsa; Mahathir Mohd Akhar; Mohamad Amierul Iqmal Mohd Muzaffar; Amirul Sharafuddin Ahmad Faizal (Multidisciplinary Applied Research and Innovation, 2024)
Consumers use a particular kind of liquid called cooking oil for cooking. Palm oil is one of the cooking oils that people select. According to the report, improper disposal of used cooking oil will pollute the ecosystem. Unchecked environmental pollution will destroy ecosystems and have a severe effect on human life. The creation of a Mini Soaper Machine model is the major goal of this project. The first goal is to design and build a portable, user-friendly cooking oil-based book mixing and forming machine. The second goal is to research the variables that determine the motor speed of the mixer that is most effective for mixing the used cooking oil, comparing the length of time required to harden the mixture between the traditional method and the hardening process using a heater, as well as the productivity of soap production between the traditional method and the Soaper Mini Machine. In conclusion, 150 rpm is the ideal mixing motor speed and can produce a quality mix in about 10 minutes. Additionally, employing a heater to solidify the mixture is superior to the conventional procedure. This is so that the mixture can solidify in just 2 hours and 30 minutes if a heater is used, and thus the soap can be used immediately as opposed to the conventional approach, which requires the soap to undergo a one-month curing process before it can be used, as well as 24 hours for the purpose of hardening. As a result of time savings of up to 67% when compared to using an egg beater and up to 50% when compared to an automatic stirrer, the study further demonstrated that this machine is capable of increasing soap manufacturing productivity when compared to conventional methods. When compared to the conventional method, the heater can cut the time